Sistem Informasi Manajemen Jual-Beli Di Grosir Buah UD. Sumber Buah Berbasis Web (Studi Kasus : Ud. Sumber Buah Pasar Gede Solo) - Suharto, Yanuar Bagus; , Aris Rakhmadi, S.T., M. Eng (2015)
Now is the era of computerized technology, more and more people computer users who use various applications to facilitate everyday activities they tend chose something instant, secure and efficient. no exception in buying and selling things. Modeled on the management of online advertising buying and selling in 2015 is extremely in the example case of a website visitor enjoy doing "olx.co.id" and "berniaga.com" or still many others are ordinary people too easily open the stall and into admin ad account its own, the average selling advertising on the website was successful in buying and selling activities because greatly facilitate the activities of the community to meet their daily needs. Admin management modeled on the computerization of sales mentioned above, then to data processing facilitate the buying and selling fruit at UD. Sumber Buah Pasar Gede Solo also requires the management of information systems. The case of problems the author designed and built a management information system of buying and selling in the wholesale fruit UD. Sumber Buah web-based PHP programming language created on the computer with the Windows operating system by using the application editor "Notepad ++", the reasons wear Notepad ++ because this application can be downloaded for free and have a rule rules which is easily understood, then use the "Appserv" to cultivate localhost its database with the judgment has the best accuracy compared to database server the other, and has a high capacity to be able to run on multiple operating systems different. Using the "MySql" as database management for MySQL has a command and the rules are relatively simple to use, with the nature of open source and flexible. Keyword: Appserv, MySql, Notepad ++, PHP